2020
DOI: 10.1177/0363546519899923
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Intra-articular Mesenchymal Stromal Cells for the Treatment of Knee Osteoarthritis: A Double-Blinded Prospective Randomized Controlled Clinical Trial

Abstract: Background: Currently, there are limited nonoperative treatment options available for knee osteoarthritis (OA). Cell-based therapies have emerged as promising treatments for knee OA. Autologous stromal vascular fraction (SVF) has been identified as an efficient medium for intra-articular administration of progenitor cells and mesenchymal stem cells derived from adipose tissue. Hypothesis: Patients receiving intra-articular SVF would show significantly greater improvement than patients receiving placebo injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
199
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(201 citation statements)
references
References 23 publications
1
199
0
1
Order By: Relevance
“…It can be considered a successful regeneration of the articular cartilage if a formation of hyaline cartilage can be found on the surface of the joints. Previous studies have shown the de novo formation of hyaline-like cartilage after treatment with ASCs and umbilical cord blood-derived MSCs [24,25]. The second occurrence that could be observed on the MRI images was a widening of the joint space 14 months after the SVF treatment.…”
Section: Pearson Correlation Coefficient (R)mentioning
confidence: 74%
See 1 more Smart Citation
“…It can be considered a successful regeneration of the articular cartilage if a formation of hyaline cartilage can be found on the surface of the joints. Previous studies have shown the de novo formation of hyaline-like cartilage after treatment with ASCs and umbilical cord blood-derived MSCs [24,25]. The second occurrence that could be observed on the MRI images was a widening of the joint space 14 months after the SVF treatment.…”
Section: Pearson Correlation Coefficient (R)mentioning
confidence: 74%
“…In both treatment groups, an improvement of the clinical parameters was observed. In the case of this study, the effects were dose-dependent, with higher dose showing higher effects [25]. In this case series, we did not administer predefined numbers of SVF cells but the maximum number that could be collected from each patient's tissue, which was on average 7.56 × 10 6 SVF cells.…”
Section: Discussionmentioning
confidence: 94%
“…MSC-based therapy to treat OA has received attention based on promising pre-clinical reports. Various cell sources have been successfully used in early-phase clinical trials, including bone marrow (Orozco et al, 2014;Vega et al, 2015;Soler et al, 2016), umbilical cord (Matas et al, 2019), and adipose-derived stromal vascular fraction (Garza et al, 2020). A recent systematic review summarizing available studies testing intra-articular MSC therapy for OA and chondral defects concluded that the therapy is safe with clinical and in some cases imaging improvement (McIntyre et al, 2018).…”
Section: Efforts To Translate Pre-clinical Findings Into Clinical Promentioning
confidence: 99%
“…These preclinical “proof of principle” analyses have determined that both freshly isolated and cryopreserved human ASCs can accelerate and enhance the rate of skin wound healing [ 48 ] ( Figure 1 ). Indeed, by performing the isolation procedure on lipoaspirates harvested at the time of a single operation and immediately implanting the recovered cells, regulators have authorized such autologous adipose cell products to advance into clinical trials [ 49 ]; however, to date, none of these devices are used routinely in the United States as a basis for skin wound therapy. Furthermore, while sophisticated adipose-derived cell therapies are feasible as elective procedures in a civilian hospital of an industrialized country, these would not be practical in less advanced environments, such as a poorly resourced hospital in a developing nation or under conditions encountered on the battlefield.…”
Section: Adipose-derived Cellsmentioning
confidence: 99%